1991
DOI: 10.1113/jphysiol.1991.sp018707
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular analysis of inherent and synaptic activity in hypothalamic thermosensitive neurones in the rat.

Abstract: SUMMARY1. Intracellular neuronal activity was recorded in rat preoptic-anterior hypothalamic tissue slices. Thirty neurones were classified as warm sensitive, cold sensitive or temperature insensitive, based on their firing rate response to temperature changes. Seventy-seven per cent of the neurones were temperature insensitive, which included both spontaneously firing and silent neurones. Of all neurones, 10% were warm sensitive and 13% were cold sensitive.2. Silent temperature-insensitive neurones had lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
64
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 14 publications
4
64
0
Order By: Relevance
“…Regardless of neuronal type, resistance increased with cooling and decreased with warming. Other studies have shown similar thermal effects on the resistances of hypothalamic neurones (Curras et al 1991), hippocampal neurones (Thompson, Masukawa & Prince, 1985) and spinal motoneurones (Pierau, Klee & Klussmann, 1976). Like Fig.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Regardless of neuronal type, resistance increased with cooling and decreased with warming. Other studies have shown similar thermal effects on the resistances of hypothalamic neurones (Curras et al 1991), hippocampal neurones (Thompson, Masukawa & Prince, 1985) and spinal motoneurones (Pierau, Klee & Klussmann, 1976). Like Fig.…”
Section: Discussionmentioning
confidence: 75%
“…A different theory of neuronal thermosensitivity comes from another intracellular recording study of rat POAH tissue slices (Curras, Kelso & Boulant, 1991 (Purves, 1981), and this appears to be the case in previous studies. …”
mentioning
confidence: 99%
“…The second, most commonly recognized as truly thermosensitive, is pacemaker-or prepotential-driven, with neurons that fire almost rhythmically as illustrated in Fig. 1A (7,9,15).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that the depolarizing prepotentials which precede an action potential shorten with warming, thus reducing the interspike interval and increasing the firing rate (7,9). An A-type K ϩ current, which regulates the firing rate in other neuronal types, could be responsible for the shortening of the prepotential's duration (9), because it activates and inactivates faster at higher temperatures.…”
mentioning
confidence: 99%
“…LTS potentials were identified in a proportion of these cells; however, precise cytoarchitectural sites of recordings were not determined histologically . Another group recently recorded intracellularly from thermosensitive neurons in the medial preoptic area-anterior hypothalamus of the rat (Curras et al 1991). However, the locations of these recordings…”
Section: Introductionmentioning
confidence: 99%